Significant histological changes are not rare in indeterminate‐phase chronic hepatitis B patients with hepatitis B e antigen‐negative and normal alanine aminotransferase levels - Deliang Huang; Guangde Zhou; Jinghan Peng; Qinxian Cai; Guojun Li; Hong Yu; Zhibing Zhu; Yuanyuan Chen; Huiyi Lai; Jinyan Jiang; Hong Yu; Jun Chen (iLabmed)
Abstract Background & Objectives The degree of liver injury in indeterminate chronic hepatitis B (CHB) infection patients with Hepatitis B e antigen(HBeAg)‐negative and persistently normal alanine aminotransferase (PNALT) levels is yet unclear. Therefore, we aimed to assess liver histological changes in such patients by liver biopsy and explore possible predictors. Methods Overall, 711 HBeAg‐negative CHB patients with PNALT levels who underwent liver biopsy from January 2017 to June 2022 were included in this retrospective study. The relationships between histological changes and predictors were assessed by smooth curve fitting and multivariate logistic regression analysis models. Data were also analyzed using American Association for the Study of Liver Disease (AASLD) modified alanine aminotransferase (ALT) criteria. Results The proportion of significant histological changes in the indeterminate phase was higher than that in the inactive phase (53.97% vs. 41.33%). The adjusted odds ratios (aORs) of significant necroinflammation and histological changes for the indeterminate phase were 2.05 and 1.43, respectively, when compared with the inactive phase by multivariate logistic regression analyses. Significant histological changes in the‐phase were positively associated with age, ALT, Aspartate aminotransferase (AST), Hepatitis B surface antigen (HBsAg), and Hepatitis B virus (HBV) DNA levels but negatively correlated with platelet (PLT) levels. HBV DNA ≥5 log10 U/L and PLT <200 × 109/L were independent predictive factors for assessing histological changes in indeterminate‐phase patients. Similar analysis findings were obtained using the two sets of modified ALT criteria. Conclusions Significant histological changes are not rare in indeterminate‐phase CHB patients and are higher than in the inactive phase, regardless of the ALT criteria. Histological investigation is strongly suggested for intermediate stage patients with HBV DNA >5 log10 U/L or PLT <200 × 109/L and antiviral therapy should be considered for such patients.